CLUSTERED PRIMARY BRANCH 1, a new allele of DWARF11, controls panicle architecture and seed size in rice. Issue 1 (28th April 2015) - Wu, Yongzhen; Fu, Yongcai; Zhao, Shuangshuang; Gu, Ping; Zhu, Zuofeng; Sun, Chuanqing; Tan, Lubin
Summary: Panicle architecture and seed size are important agronomic traits that directly determine grain yield in rice ( Oryza sativa L.). Although a number of key genes controlling panicle architecture and seed size have been cloned and characterized in recent years, their genetic and molecular mechanisms remain unclear. In this study, we identified a mutant that produced panicles with fascicled primary branching and reduced seeds in size. We isolated the underlying CLUSTERED PRIMARY BRANCH 1 ( CPB1 ) gene, a new allele of DWARF11 ( D11 ) encoding a cytochrome P450 protein involved in brassinosteroid (BR) biosynthesis pathway. Genetic transformation experiments confirmed that a His360Leu amino acid substitution residing in the highly conserved region of CPB1/D11 was responsible for the panicle architecture and seed size changes in the cpb1 mutants. Overexpression of CPB1 / D11 under the background of cpb1 mutant not only rescued normal panicle architecture and plant height, but also had a larger leaf angle and seed size than the controls. Furthermore, the CPB1 / D11 transgenic plants driven by panicle‐specific promoters can enlarge seed size and enhance grain yield without affecting other favourable agronomic traits. These results demonstrated that the specific mutation in CPB1 / D11 influenced development of panicle architecture and seed size, and manipulation of CPB1 / D11 expression using the panicle‐specific promoter could be used to increase seed size, leading to grain yield improvement in rice.